Analysis of the Application of Parenting Activities in Hope Kindergarten Bunda Karak Woyla Barat - Nurma Nurma; Raden Rachmy Diana; Na'imah Na'imah; Fidya Ismiulya; Desi Farijah (AL-ISHLAH: Jurnal Pendidikan, 2023)
The phenomenon in the Alpha generation has many challenges in parenting. Children's daily life cannot be separated from digital devices is one of the factors that have the potential to affect children's growth and development. The challenge of the digital age is because these digital devices are very neutral which has a positive as well as negative impact on their users. This study aims to analyze the application of parenting activities in Harapan Bunda Karak Kindergarten using descriptive qualitative research methods. Data collection used observation techniques, interviews with the principal, two class teachers and two parents of students of Harapan Bunda Karak Kindergarten with interview guidelines in the form of unstructured interviews. Data analysis through the process of reducing the data obtained, presenting data, and finally drawing conclusions. The results showed that the involvement of parents in early childhood education in parenting activities is still in the category of lack of this, as can be seen from the process of involving parents in the classroom when learning activities have not been implemented. Parental involvement is still in orientation activities, religious events and field trips.  Obstacles in implementation come from parental and school factors. The application of digital parenting in Harapan Bunda Karak Kindergarten has also not been implemented. The importance of implementing digital parenting in schools is something that must be considered considering the current condition that children cannot be kept away from digital devices in a hurry. The solution to the dangers of digital devices for children is through the application of digital parenting